2022
DOI: 10.1021/acsphotonics.2c00551
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Reflection Induced in Reciprocal Hyperbolic Materials

Abstract: Reflection is one of the most fundamental properties of light propagation. The ability to engineer this property can be a powerful tool when constructing a variety of now ubiquitous optical and electronic devices, including one-way mirrors and antennas. Here, we show from both experimental and theoretical evidence that highly asymmetric reflection can be induced in reciprocal hyperbolic materials. This asymmetry stems from the asymmetric cross-polarization conversion between two linearly polarized waves, an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 63 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…In this case, the reflection asymmetry comes from a cross-polarization conversion between TM and transverse electric (TE) waves. 67 It would be noteworthy to discover the kinds of asymmetric transmission and absorption possible with an asymmetric reflection spectrum.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this case, the reflection asymmetry comes from a cross-polarization conversion between TM and transverse electric (TE) waves. 67 It would be noteworthy to discover the kinds of asymmetric transmission and absorption possible with an asymmetric reflection spectrum.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Besides, there is a FR related with the negative part of δ spectra, providing further degree for the manipulation of NLP. The azimuthal angle (ϕ) performs the function of an index of polarization orientation, which as a consequence could lead to modification of the peak value of δ [38,62]. To explore the impact of ϕ, δ spectra versus λ and ϕ is simulated and shown in figure 5, where d 1 = d 2 = 0.1 µm and t = 0.25 µm.…”
Section: Tunable Nlp With Incidence and Azimuthal Anglesmentioning
confidence: 99%
“…Such ENZ modes have been widely reported in natural hyperbolic plasmonic materials and twisted bilayer systems. Wu et al further demonstrated experimentally and theoretically that natural hyperbolic films can support highly asymmetric reflection, which can be tuned by the film thickness [294] .…”
Section: • Asymmetric Transmissionmentioning
confidence: 99%